Elizabeth Parker’s Sampler/Diary: The Autobiographical Needle - Róisín Quinn-Lautrefin (Cahiers Victoriens et Edouardiens)
Relying on an unusual stitched text made by a young servant in the 1830s, this essay sets out to explore the Victorian sampler as a didactic tool designed to inculcate desirable behaviour as well as literacy and numeracy in young girls. Often viewed as repetitive exercises designed to enforce social norms of femininity, however, samplers could paradoxically prove to be spaces for girls to express their individualities and subjectivities.